The level of services provided to children with disabilities in kindergartens from the point of view of their mothers - Al-Tal, Suhair Mamdouh; Aleid, Wafaa Ayed; Al-Jawaldeh, Fuad Eid; Masoud, Wael Mohammad Mousa (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the level of services provided to children with disabilities in kindergartens from the point of view of their mothers, and to achieve the objectives of this study, a descriptive and analytical approach was adopted, A tool, consisting of (30) items, has also been developed to identify the level of services provided to children with disabilities and the indications of its validity and reliability have been verified. The sample of the study included (370) mothers of disabled children in kindergartens in Cairo governorate. The researchers have reached many results, the most important of which were: The level of services provided to children with disabilities in kindergartens from the viewpoint of their mothers was (average), with a mean of (2.83), and a standard deviation (.473). The results also indicated that there were no statistically significant differences at the level of significance (0.05) about the level of services provided to children with disabilities in kindergarten according to the variables of the social status and educational qualification, while there were statistically significant differences at the level of significance (0.05) according to the age variable and that In the first axis: (rehabilitative services, and the general average), and the Statistical differences were in favor of mothers under the age of 25. The study recommended providing qualified people to work with children with disabilities in kindergartens, in addition to providing the necessary financial support to improve the services provided to these children.